One hundred and fifty years of rowing faster - Seiler, S. (Sportscience, 2006)
Boat velocity has increased linearly by 2-3% per decade since the first Oxford-Cambridge boat race in 1829. Part of this increase is a result of recruitment of athletes from a population that has become taller and stronger. However, the increase in boat speed attributable to increased physical dimensions alone accounts for less than 10% of the total improvement, because the increase in rower mass has increased boat drag. A 10-fold increase in training load over the last 150 years probably accounts for about one-third of the increase in physical capacity and performance. The rest of the improvement is due to reductions in boat drag, increases in oar blade efficiency, and improvements in rowing technique. Boat design was revolutionized in the 19th century, the only substantial change since then being a gradual reduction in boat weight. Oar design and construction have evolved steadily, the most recent development being the introduction of cleaver or "big" blades in 1991. Improvements in rowing technique have increased boat speed by reducing boat yaw, pitch and roll, and by improving the pattern of force application. New tools for real-time measurement and feedback of boat kinematics and force patterns are opening new approaches to training of individual rowers and to selection of rowers for team boats.